Tanggungjawab Perusahaan PT. Sritex terhadap Pemenuhan Hak Pesangon Karyawan yang di PHK - Deby Fatria Ntobuo; Weny Almoravid Dungga; Mohamad Hidayat Muhtar (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study aims to analyze the legal responsibility of PT Sritex in fulfilling severance pay for employees who experience termination of employment (PHK) due to the company's bankruptcy. The method used is the normative legal research method, namely a method that relies on the analysis of laws and regulations, legal doctrine, and literature relevant to the subject matter. Data sources were obtained from primary legal materials such as the Civil Code, Law Number 13 of 2003 concerning Manpower, and Law Number 6 of 2023 concerning Job Creation, as well as secondary legal materials in the form of books, scientific journals, and other academic writings. The analysis was carried out qualitatively to examine and formulate legal arguments regarding the company's obligations in guaranteeing workers' normative rights. The results of the study show that PT Sritex is legally obliged to provide severance pay to workers who are laid off, as regulated in the principles of contract law, the principle of justice, and national statutory provisions. This obligation remains in effect even though the company is bankrupt. In addition, international norms such as the UN Guiding Principles and ILO conventions reinforce the importance of corporate commitment to fulfilling basic workers' rights ethically and sustainably. This study has limitations because it has not explored empirical realities in the field. Therefore, further research is recommended to explore aspects of the implementation of corporate responsibility directly and form a more adaptive legal protection system in situations of economic crisis.